Peningkatan Kedisiplinan Dalam Proses Belajar Mengajar Melalui Pembinaan Etos Kerja Guru Di SMP Negeri 5 Kepenuhan - Zulkhoiri Zulkhoiri (STKIP ROKANIA, 2022)
This research is designed to help improve teacher discipline in carrying out teaching activities and in line with teacher professional ethics. The research in the form of a School Action Study (PTS) was conducted in two cycles, each of which was conducted in two sessions. Each cycle consists of four phases, namely planning, implementation, observation and reflection. The data collection technique was done by filling out the observation form during the action research. Based on the results of the study, it can be concluded that the application of professional ethics development by the principal is very helpful for SMP Negeri 5 Speed teachers to further improve their self-quality and performance management in terms of discipline awareness. Implemented in the teaching and learning process in the classroom.